Fruit Fly Parasitoid on Snake Fruit: Morphological and Molecular Identification, Parasitism Rate and Mass Rearing Method Comparison - Willing Bagariang; Yuris Tiyanto; Ani Widarti; Atep Budiman; Didah Mahmudah; Ranti Riama Pardede; Novita Tiarasari (Universitas Wiralodra, 2026)
Fruit flies (Diptera: Tephritidae) are major pests of horticultural crops reducing fruit quality and limiting export opportunities due to quarantine restrictions in many importing countries. Developing environmentally sustainable pest management strategies is therefore essential to enhance the competitiveness of Indonesian horticultural products. This study aimed to identify fruit fly parasitoid on snake fruits, level of parasitism and to find a feasible mass-rearing method under laboratory conditions. Fruit fly parasitoid was collected from snake fruits in Magelang, Central Java and Sleman, Special Region of Yogyakarta followed by laboratory rearing, morphological and molecular identification and comparison of mass rearing methods using natural host fruits and modified artificial diet. Morphological and molecular identification showed that parasitoid parasitized fruit fly on snake fruits was identified as Fopius arisanus (Hymenoptera: Braconidae). F. arisanus associating with fruit fly that was morphologically identified as Bactrocera carambolae (Diptera: Tephritidae). The average field parasitism rate of F. arisanus on fruit fly infesting snake fruits was 27.38%, with sex ratio of males and females were 43.89% and 56.11%). Mass rearing method using natural host fruits (snake fruits) showed successfully parasitizing on fruit fly eggs and resulted sex ratio of males and females were 42.1% and 57.9%, whereas rearing method using the modified artificial host showed no parasitizing on fruit fly eggs and should be further studied and developed. These findings support F. arisanus as a potential biological control for fruit fly management programs in Indonesia.